2018
DOI: 10.2106/jbjs.17.01677
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Depression on Patient-Reported Outcomes After Total Joint Arthroplasty Is Modulated by Baseline Mental Health

Abstract: Background: Depression and poor mental health are known to be negative predictors of patient-reported outcomes after total joint arthroplasty. Although previous studies have examined these risk factors in isolation to each other, they are, in reality, closely related, and yet each represents a different aspect of one’s psychological well-being. The objective of this study was to investigate the association between depression and patient-reported outcomes, taking into account patients’ baseline ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Better metrics and outcomes are also needed to determine how active a particular psychiatric disorder may be at the time of surgery. Halawi et al 13 completed a prospective study to determine whether baseline mental health affected outcomes in patients with depression who were undergoing TJA. He found that patients with depression had significant improvements in outcome post-operatively, but these gains were modulated strongly by mental health at the time of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Better metrics and outcomes are also needed to determine how active a particular psychiatric disorder may be at the time of surgery. Halawi et al 13 completed a prospective study to determine whether baseline mental health affected outcomes in patients with depression who were undergoing TJA. He found that patients with depression had significant improvements in outcome post-operatively, but these gains were modulated strongly by mental health at the time of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diagnoses of depression, anxiety or depression and anxiety have been shown to have inferior outcomes [ 5 , 28 , 29 ]. In terms of depression alone, studies estimated a prevalence of 22%-28% in the TJA population [ 4 , 30 ]. These patients have an increased risk of readmission [ 21 , 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This notion was recently demonstrated in THA and TKA patients by Halawi et al, who showed that poor baseline mental health as measured by SF-36 MCS scores was a more significant negative prognostic indicator than a diagnosis of depression itself. 9 It is important to note that a diagnosis of depression in our study was obtained via chart review and does not identify whether the depression is treated. Treatment of depression may potentially lessen the effect of the diagnosis on SF-36 MCS scores and TAA outcomes.…”
Section: Discussionmentioning
confidence: 99%